Respostas

A melhor resposta!
2013-09-14T16:05:20-03:00
A) x2-3x-10
a = 1
b = -3
c = -10
b² - 4ac

-3² - 4. 1.-10
9 + 40
49

-b +- raiz de 49/2.a

3 + 7 / 2.1
10/2


3 - 7 / 2.1
-4 / 2
-2

S= {5,-2]

b= x2+x-20
a = 1
b = 1
c = -20

1² - 4.1.-20
1+80
81

-1 + raiz de 81 / 2a
-1 + 9 / 2
+10 / 2
5

-1 - raiz de 81 / 2a
-1 - 9 / 2
- 10 /2
-5

s={5,-5}

c=x2+4x-4
a = 1
b = 4
c=-4
-4² - 4 . 1. -4
16 + 16
32

não tem raizes .
1 5 1
2013-09-14T16:05:35-03:00
Só fazer por baskara
x2-3x-10= 0 
-b+ou- raiz de delta/2a
delta = b²-4ac
entao vamos la
-(-3) +-raiz(-3)²-4.1.-10/2
3+-raiz9+40/2
3+-raiz 49 /2
3+-7/2
ai faz separado 3+7/2=10/2=5
3-7/2=-4/2=-2
raizes 5 e -2
b)x²+x-20=
-1+- raiz 1²-4.1.-20/2.1
-1+-raiz81/2
-1+-9/2
-1+9/2= 8/2=4
-1-9=-10/2=-5
raizes 4 e -5
c)x²+4x-4
-4+ou- raiz4²-4.1.-4/2.1
-4+-raiz32/2
-4+-4raiz2/2
-4+4raiz2/2=-4+2raiz2
-4-4raiz2/2=-4-2raiz2
raizs -4+2raizde2 e -4-2raiz de 2